Wnioskowanie materialne z perspektywy inferencjalizmu znaczeniowego Roberta B. Brandoma - Kublikowski, Robert (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In a natural language there are inferences which are difficult to express by means of a formal language. The goal of this article is to answer the question: what are such inferences, sometimes called “material inferences”? Material inferences are correct not only by means of their logical form but mainly on the basis of the content (meaning) of nonlogical vocabulary which is used in such inferences. Formal inferences are correct only on the basis of their logical form. Various, sometimes controversial examples of such inferences are presented and analysed in the article. Some of them were given by Robert B. Brandom in his meaning inferentialism inspired by the ideas of Wilfrid Sellars. Brandom challenges the existing theory of inference in which a logical form is acknowledged as a basis of correctness of inference. He emphasises that the essential condition of a material inference is an understanding of a content of expressions which inform not only about formal relations but mainly about informal (material) relations. Formal and material inferences are governed by formal and material conditions of correctness. A formal condition of correctness of a formal inference relies on a logical consequence which relates premises and a conclusion. In the case of a material inference such a condition is fulfilled if premises and a conclusion are connected by a consequence which cannot be expressed only by logical vocabulary. A material condition is obligatory for both types of inferences and it requires premises and a conclusion to be true.